IS A FOOD SECURITY PROGRAM A SOLUTION IN FAMILY ECONOMIC RESILIENCE? - Zenita Afifah Fitriyani (Mega Aktiva, 2022)
The Covid-19 pandemic has had a tremendous impact on the health and economy of families, therefore, one of the things that needs to be  maintened during the Covid-19 pandemic  is choosing needs, maintaining cleanliness and food health  so that it not contaminated by bacteria, germs, and harmful subtances. Which can pose a threat to health. Food needs are currently a big problem for the community, because the impact of the Covid-19 pandemic on family food nees has changed consumption pattern from shopping, processing and consuming food product, so it is necessary to pay attention to family groups who are vulnerable to problems with food products to thethreat of hunger. İn addition, the family financial recession due to the Covid-19 pandemic requires people to have the ability to face change so that family economic resilience is getting better. The purpose of this study was to analyze food security programs and family economic resilience during the Covid-19 pandemic. The method used in data analysis is a qualitative method with a Systematic Literature Review (SLR), in which the research uses books, national and international journals, related articles, and other literature that is searched, selected, and analyzed. The result of this research is the need to build food security and family economic resilience amid the food crisis that hit during the Covid-19 pandemic. In addition, it is necessary to diversify the sources of livelihoods to meet food and non-food needs, so that the economic resilience of the family also increases.